Photonuclear reactions on p-shell nuclei at intermediate energies - Khodyachikh, A.F. (Вопросы атомной науки и техники, 2003)
Absolute total and differential cross sections for (g,р)-, (g,n)- and (g,pn)- reactions on the ¹²С, ¹⁴N and ¹⁶О nuclei have been measured using a diffusion chamber placed in a magnetic field and irradiated by a beam of bremsstrahlung photons with an end-point energy of 150 MeV. The applicability of photoabsorption model on a correlated proton-neutron pair was proved. It is concluded that models with essential contribution of meson exchange currents provide a qualitative description of energy dependence of total and differential cross sections at energies above 50 MeV. За методом дифузійної камери у магнітному полі на гальмівному пучці лінiйного прискорювача з максимальною енергією 150 МеВ виконано вимірювання енергетичної залежності повного та диференційного перерезів каналів (g,р)-, (g,n)- і (g,pn)- реакцій на ядрах ¹²С, ¹⁴N и ¹⁶О. Обговорюється роль нуклонних кореляцій у проміжній області енергій. Зроблено висновок про переважаючу роль обмінних мезонних струмів при фотоутворенні високозбуджених станів проміжних ядер, починаючи від енергій вище 50 МеВ. Методом диффузионной камеры в магнитном поле на тормозном пучке линейного ускорителя с максимальной энергией 150 МэВ выполнены измерения энергетической зависимости полного и дифференциальных сечений каналов (g,р)-, (g,n)- и (g,pn)- реакций на ядрах ¹²С, ¹⁴N и ¹⁶О. Обсуждается роль нуклонных корреляций в промежуточной области энергий. Сделан вывод о преобладающей роли обменных мезонных токов при фотообразовании высоковозбужденных состояний промежуточных ядер, начиная с энергий выше 50 МэВ.